PENGARUH METODE PENYIMPANAN TERHADAP MUTU BENIH KACANG BAMBARA (Vigna subterranea L.) - Erica Tira Mutia; Sari Sari; Okti Syah Isyani Permatasari (BPFP Universitas Bengkulu, 2024)
[EFFECT OF STORAGE METHOD ON QUALITY OF BAMBARA GROUNDNUT (Vigna subterranean L.) SEEDS]. Bambara groundnut is a legume that has potential as a food crop. Bambara groundnut seeds are usually stored in their pods. The used of pod storage can reduce storage capacity and increase seed weight on distribution. This research aims to study the effect of pods and packaging types on the viability and vigor of bambara groundmut seeds so as to obtain a safe and efficient storage method. A randomized complete design was employed, consisting of two factors. The first factor was the seed storage method (four levels): seeds with pods in PP-plastic, seeds with pods in plastic sack, seeds without pods in PP-plastic, and seeds without pods in plastic sack packaging. The second factor was storage period: 1 to 6 months. Storage was carried out in a room at 20 °C and RH 65%. The results showed that plastic packaging is absolutely necessary to maintain seed moisture content (mc) because the pods could not maintain it. Seed in plastic sack packaging had mc of 11,1% - 11,4%, while initial seed has mc of 9,0%, seed stored in PP-plastic had mc of 9,4% - 9,6%. Pod removal suppressed fungal infection. Fungal infection of seeds stored in plastic packaging without pod (17,11%) was lower than seed with pods (44,00%). Vigor of seed stored without pods in PP-plastic was better than others. Moreover, storage of bambara groundnut seeds without pods can reduce storage space requirements (64,62%) and reduce seed transportation weight (25,89%). Bambara seed should be extracted from the pod and save in PP plastic packaging in order to keep the seed vigor and efficient in storage requiirement.